Proud to be Bolivian: Visibility Fights Xenophobia in Buenos Aires - Gavazzo, Natalia (2014)
There was a time in Buenos Aires when bolivians were often victims of hate crimes. They huddled in their working-class neighborhoods, hoping they might be confused with others from Argentina´s north. Those times are changing, and fiestas -as well as legal reforms- have helped make the Bolivian community visible in a positive way.